2001
DOI: 10.1080/10903120190939995
|View full text |Cite
|
Sign up to set email alerts
|

F Ailed P Rehospital I Ntubations : A N a Nalysis of E Mergency D Epartment C Ourses and O Utcomes

Abstract: Paramedic intubation failures result from a variety of factors. Less than half of field intubation failures were remedied in the ED by the use of neuromuscular-blocking agents. A similar number were intubated without the use of RSI. A fraction of failed field ETIs may have resulted from inadequate operator training or experience. A small percentage of field patients were "truly difficult" and required advanced resources in the ED to facilitate airway management. Medical directors should be cognizant of the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…Recent data suggest an adverse effect of paramedic intubation on outcome, including a separate analysis using traumatic-brain-injury data from our own out-of-hospital system (Davis et al, unpublished data). [57][58][59][60][61][62][63][64][65][66] The potential reasons for improved outcomes in aeromedical patients warrant some discussion. The results reported here may reflect the benefit of greater experience with advanced procedures or optimal monitoring during ventilation of patients with severe traumatic brain injury.…”
Section: Discussionmentioning
confidence: 98%
“…Recent data suggest an adverse effect of paramedic intubation on outcome, including a separate analysis using traumatic-brain-injury data from our own out-of-hospital system (Davis et al, unpublished data). [57][58][59][60][61][62][63][64][65][66] The potential reasons for improved outcomes in aeromedical patients warrant some discussion. The results reported here may reflect the benefit of greater experience with advanced procedures or optimal monitoring during ventilation of patients with severe traumatic brain injury.…”
Section: Discussionmentioning
confidence: 98%
“…Unrecognized misplaced intubation has been documented as an issue in EMS since 1984, with early studies showing a unrecognized misplaced intubation rate of 0.4% to 8%. [1][2][3][4][5][6][7][8] A previous study from 1997, conducted at the same regional Level I trauma center emergency department (ED) as our study, reported an unrecognized misplaced intubation incidence of 25%. 9 Most recently, unrecognized misplaced intubation rates of 7% and 10% have been reported.…”
Section: Introduction Backgroundmentioning
confidence: 85%
“…The incidence of unrecognised oesophageal intubation is dependent on whether neuromuscular blocking agents have been used or not. In two studies of drug-assisted field intubation performed by paramedics, the reported rate was as low as 0.4% (55,56). Conversely, in other studies of paramedic field intubation where drugs were not used, the rate of unrecognised oesophageal intubation was 6% (57) and 16.7% (58), respectively.…”
Section: Complicationsmentioning
confidence: 91%